Principal Leadership: Responding to The Challenges of 21st Century Teacher Competence - Supadi, Supadi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to understand the principal's leadership in responding to the challenges of the pedagogic competence of 21st-century teachers at SMA Negeri 68 Jakarta. A qualitative approach with a descriptive method is applied in this study. Data was collected through interviews, observation, and documentation. The data analysis was conducted interactively, starting with data collection, data reduction, data display, and concluding. The results showed that; Principal leadership in improving teacher pedagogic competence is carried out by strengthening educator certification, training organized by the department and school, strengthening collaboration, communication, critical and creative thinking, implemented through literacy skills, strengthening character education, information, and communication technology-based learning. This research has implications for the importance of teacher competence in improving the quality of education in schools, so it needs to get earnest attention from all parties.